2015
DOI: 10.4269/ajtmh.14-0660
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Utilization of Health Extension Workers in the Context of Scale-Up of Integrated Community Case Management of Childhood Illnesses in Ethiopia

Abstract: Ethiopia has invested significant resources in integrated community case management (iCCM) of childhood illness. In Oromia Region, iCCM scale-up was phased in, allowing for comparisons between districts providing iCCM and routine services. We assessed the determinants of utilization of health extension workers (HEWs) delivering iCCM services at rural health posts by caregivers of sick, under-five children in a cross-sectional survey. We found low utilization of HEWs with only 9.3% of caregivers of a child sick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 33 publications
7
48
0
Order By: Relevance
“…Predisposing factors, such as health beliefs, education and other user characteristics, have been found to determine the use of preventive and curative health services [ 25 , 44 , 46 ]. Consistent with findings from other studies on utilization of maternal health service [ 25 , 26 , 42 , 43 ] and integrated community case management of childhood illness [ 28 ], we found that maternal education was strongly associated with higher MTBT service utilization, particularly one-time use and for achieving minimum number of visits. Mothers with a higher level of education may be more informed and have greater awareness of or capacity to understand health problems experienced by their children as well as the benefits of health care services, which may lead to more effective use of information and to optimal health-seeking behavior [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Predisposing factors, such as health beliefs, education and other user characteristics, have been found to determine the use of preventive and curative health services [ 25 , 44 , 46 ]. Consistent with findings from other studies on utilization of maternal health service [ 25 , 26 , 42 , 43 ] and integrated community case management of childhood illness [ 28 ], we found that maternal education was strongly associated with higher MTBT service utilization, particularly one-time use and for achieving minimum number of visits. Mothers with a higher level of education may be more informed and have greater awareness of or capacity to understand health problems experienced by their children as well as the benefits of health care services, which may lead to more effective use of information and to optimal health-seeking behavior [ 14 ].…”
Section: Discussionsupporting
confidence: 91%
“…The selection of factors potentially associated with service utilization was guided by the conceptual framework ( Fig 2 ) adapted from the behavioral model of health services utilization developed by Andersen [ 23 , 24 ]. This model has been used widely for empirical research on utilization of maternal health services [ 25 27 ], integrated community case management of childhood illness [ 28 ], and medical care [ 29 ]. The model proposed that use of health services is a function of characteristics of both individual user and the health system.…”
Section: Methodsmentioning
confidence: 99%
“…There were, however, concerns that the utilisation of iCCM services was low . The reasons included absent HEWs at the health posts, little trust in the HEWs , perceptions of which illness severity they could manage, the quality of their services , lack of community awareness of services provided at the health post , limited skills of HEWs in the management of sick children and lack of drugs and other supplies .…”
Section: Introductionmentioning
confidence: 99%
“…The final weakness to be discusses is that we did not include costs of demand generation, although evidence suggests that demand side barriers are major causes of sustained low intervention coverage [25,26]. To focus on demand generation would be especially appropriate in Ethiopia where community health workers have already been deployed throughout the country but the utilization of key health services remains low [26].…”
Section: Discussionmentioning
confidence: 99%